Method for testing 180-degree initial stripping force of auxiliary material of polaroid

Through the 180° initial peeling force testing method, the problem of peeling force uncertainty of polarizer auxiliary materials is solved, more accurate detection and stable data results are achieved, customer costs are reduced, and production efficiency is improved.

CN119223866APending Publication Date: 2024-12-31SHENZHEN SAPO PHOTOELECTRIC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411329866.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The peeling force uncertainty of the protective film and release film of the polarizer during the tearing process leads to difficult situations for customers to tear when using it, affecting production efficiency.

Method used

Using the 180° initial peel force test method, by setting zones A and B on the glass, cutting polarizer samples and using traction tape for tensile testing, the maximum test value is recorded to evaluate whether the peel force meets customer requirements.

Benefits of technology

This method can more accurately detect the adhesive performance of polarizer auxiliary materials, provide reliable data results, avoid bad auxiliary materials flowing to the client, reduce customer usage costs, and improve production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119223866A_ABST
    Figure CN119223866A_ABST
Patent Text Reader

Abstract

The invention provides a method for testing 180-degree initial stripping force of a polarizer auxiliary material, which comprises the following steps of: preparing a piece of glass which is divided into an area A and an area B, arranging a release layer on the surface of the area B, and ensuring that the length of the area A is not less than that of the area B; cutting the polaroid at 0 degree to obtain a test sample, wherein the width of the test sample is not greater than the width of the area A; attaching a test sample to the area A, wherein the gap between the test sample and the release surface of the area B is less than 0.5 mm; the thickness of the test sample is greater than that of the release layer; the two ends of a traction adhesive tape are bonded to the tail end of the traction film and the starting end, close to the B area, of the test sample respectively, a sample piece to be tested is obtained, and the distance L1 between the traction film and the test sample is larger than 10 mm and smaller than or equal to 50 mm; the tensile strength of the traction adhesive tape is 240-290 MPa; and performing a stripping force test. By adopting the technical scheme of the invention, a relatively stable data result can be obtained, and a detection result is reliable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polarizer testing, and in particular to a method for testing the 180° initial peeling force of a polarizer auxiliary material. Background Art

[0002] Polarizers are used in OLED and LCD display modes. Polarizers contain protective film and release film as auxiliary materials, which play a role in process protection. When polarizers are attached to the polarizers, downstream clients will tear off the auxiliary materials. At this time, the protective film and release film are required to be easy to peel off during the tearing process. However, at present, the peeling force of the protective film and release film of the polarizer is uncertain, and there are differences between different manufacturers and batches of incoming materials. When customers use them, they find it difficult to tear, causing the polarizer equipment to shut down and affecting production efficiency. Summary of the invention

[0003] In view of the above technical problems, the present invention discloses a 180° initial peel force test method for polarizer auxiliary materials. Performing a 180° initial peel force test on the polarizer can better evaluate whether the peeling force meets the requirements, that is, to ensure whether the polarizer auxiliary materials (protective film, release film) can meet the easy peeling requirements required by customers.

[0004] To this end, the technical solution adopted by the present invention is:

[0005] A method for testing the 180° initial peeling force of a polarizer auxiliary material comprises the following steps:

[0006] Step S1, preparing a piece of glass for peeling force testing, wherein the glass is divided into an A region and a B region along a length direction, a release layer is disposed on the surface of the B region, and the length of the A region is not less than the length of the B region;

[0007] Step S2, cutting the polarizer at "0°" to obtain a test sample, and the end surface of the test sample has no bubbles or white edges, and the width of the test sample is not greater than the width of area A; attaching the test sample to area A, and there is no gap between the test sample and the release surface of area B; the thickness of the test sample is greater than the thickness of the release layer;

[0008] Step S3, respectively bonding the two ends of the traction tape to the end of the traction film and the starting end of the test sample near the B area to obtain a sample to be tested, wherein the distance L1 between the traction film and the test sample satisfies 10mm<L1≤50mm; and the tensile strength of the traction tape is 240-290MPa;

[0009] Step S4, vertically place the sample obtained in step S3 on the clamp of the tensile testing machine, clamp the B area of ​​the glass with the lower clamp of the tensile testing machine, clamp the starting end of the traction film with the upper clamp, start the tensile testing machine after setting the speed, and record the maximum test value.

[0010] By adopting this technical solution, a release zone is set to avoid the influence of the traction tape adhering to the glass on the test results; the thickness of the test sample is greater than the thickness of the release layer, that is, the height of the test sample is higher than the height of the release zone, so that the traction tape is firmly bonded to the end face of the test sample, avoiding errors caused by the test method; further, a traction tape with suitable tensile strength is selected (the tensile strength of the traction tape is 240-290MPa). The traction tape has a high tensile strength, which will prevent pre-tensioning. The traction tape has a low tensile strength, and the error caused by its own tensile elongation is avoided to ensure the stability of the test.

[0011] As a further improvement of the present invention, in step S1, the release layer is obtained by providing a glass coating or bonding a release film.

[0012] As a further improvement of the present invention, in step S3, the distance L1 between the traction film and the test sample satisfies 20 mm ≤ L1 ≤ 50 mm. More preferably, 20 mm ≤ L1 ≤ 30 mm. More preferably, L1 = 20 mm.

[0013] As a further improvement of the present invention, in step S3, the buffer distance between the end of the traction film and the starting end of the sample is 20 mm. This technical solution can better avoid the result being too small due to the pre-tensioning of the traction tape, and also alleviate the unstable result caused by the tape being too long.

[0014] As a further improvement of the present invention, in step S4, the speed is 300 mm / min.

[0015] As a further improvement of the present invention, when the test sample is attached to the A zone, the test sample is located in the middle of the A zone.

[0016] As a further improvement of the present invention, the width of the test sample is half of the width of the A zone.

[0017] As a further improvement of the present invention, the length of the A zone is 60-80% of the length of the glass. Furthermore, the length of the A zone is 75% of the length of the glass.

[0018] As a further improvement of the present invention, the size of the test sample is 25 mm*150 mm.

[0019] As a further improvement of the present invention, the size of the glass is 50 mm*200 mm.

[0020] As a further improvement of the present invention, the adhesive force of the traction tape is no greater than 5gf / 25mm.

[0021] As a further improvement of the present invention, the adhesive force of the traction tape is no greater than 1gf / 25mm.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] By adopting the technical solution of the present invention, the initial peeling force test design is carried out through multiple aspects, so that the bonding performance of the material can be better detected, and the test result is more reliable. Moreover, the technical solution of the present invention is easy to operate in testing the peeling force, and a relatively stable data result can be obtained, so that bad auxiliary materials can be prevented from flowing to the client, and the cost of use of the client can be reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of glass according to an embodiment of the present invention, wherein (a) is a side view and (b) is a top view.

[0025] Figure 2 Schematic diagram of glass after polarizer is attached according to an embodiment of the present invention, wherein (a) is a side view and (b) is a top view.

[0026] Figure 3 2 is a schematic diagram of an embodiment of the present invention after the two ends of the traction tape are respectively bonded to the traction film and the polarizer, wherein (a) is a side view and (b) is a top view.

[0027] Figure 4 It is a schematic diagram of a tensile test of an embodiment of the present invention.

[0028] Figure 5 1 is a state analysis diagram of the tensile test of different traction tapes according to the embodiments of the present invention, wherein (a) is an overall state diagram, and (b) is a state analysis diagram of the traction tape region.

[0029] Reference numerals include:

[0030] 1-glass, 11-area A, 12-area B; 2-test sample, 3-traction tape, 4-traction film. DETAILED DESCRIPTION

[0031] The preferred embodiments of the present invention are described in further detail below.

[0032] Example 1

[0033] A method for testing the 180° initial peeling force of a polarizing film auxiliary material and preparing a sample thereof, the steps are as follows:

[0034] Step S1, take a 50mm*200mm peeling test glass 1, the glass 1 is divided into area A 11 and area B 12, area B 12 is a release surface, and the adhesion force with the traction tape 3 is less than 5g, preferably less than 1gf / 25mm, and the release surface can be achieved by glass coating or bonding release film, such as Figure 1 shown.

[0035] Step S2, cut the polarizer sample into a size of 25mm*150mm at "0°" to obtain test sample 2. It is necessary to ensure that there are no bubbles or white edges on the end surface of test sample 2. Use a small roller to stick test sample 2 to area A 11 of glass 1. Ensure that the gap between the release surface of test sample 2 and area B 12 is less than 0.5mm. After test sample 2 is stuck to area A 11, the comprehensive height must be higher than the height of area B 12. Figure 2 Further, the bonding force between the A area 11 and the test sample 2 is preferably 1000 gf / 25 mm.

[0036] Step S3, using the traction tape 3 to bond the end of the traction film 4 and the starting end of the test sample 2 respectively, the buffer distance L1 between the end of the traction film 4 and the starting end of the test sample 2 is 20mm, such as Figure 3 Wherein, the tensile strength of the selected traction tape 3 is 240-290MPa.

[0037] Step S4, vertically place the sample to be tested on the clamp of the tensile machine, clamp the B area 12 of the glass 1 with the lower clamp of the tensile machine, clamp the starting end of the traction film 4 with the upper clamp, set the speed to 300mm / min, then start the test, and record the maximum test value, such as Figure 4 shown.

[0038] Comparative Example 1

[0039] On the basis of Example 1, the difference of this embodiment is that the traction tape 3 selected in step S3 is different. The tensile strength of the traction tape 3 selected in this embodiment is 100-150 MPa.

[0040] Comparative Example 2

[0041] On the basis of Example 1, the difference of this embodiment is that the traction tape 3 selected in step S3 is different. The tensile strength of the traction tape 3 selected in this embodiment is 450-500 MPa.

[0042] Comparative Example 3

[0043] On the basis of Example 1, the difference of this embodiment is that the traction tape 3 selected in step S3 is different. The tensile strength of the traction tape 3 selected in this embodiment is 560-610 MPa.

[0044] The peeling force test results obtained in Example 1 and Comparative Examples 1-3 are shown in Table 1.

[0045] Table 1 Peel force results of Example 1 and Comparative Examples 1-3

[0046]

[0047] Example 1 and Comparative Examples 1-3 respectively used traction tapes with different tensile strengths (indicators representing material hardness), and each was tested 5 times. The status of the test process is as follows: Figure 5 As shown, combined with the data in Table 1, it can be seen that as the tensile strength (an indicator representing the hardness of the material) increases successively, when the pull-up angle approaches 180°, it is closer to the initial peeling force of the actual peeling protective film or release film, but the traction tape of Example 1 has a low tensile strength and is prone to deformation, which will lead to inaccurate test results. The tensile strength of Examples 2 and 3 is too large, that is, the rigidity is large, and there is a possibility of pre-pulling of auxiliary materials. At the same time, it is known from the tangent results corresponding to the corresponding tensile strength that the greater the tensile strength, the test angle will deviate from 180°, which will lead to unreliable test results. Therefore, the traction tape of Example 1 is selected, that is, the tensile strength is 240-290MPa, and the test results are the most reliable.

[0048] Example 2

[0049] Based on Example 1, the difference of this example is that in step S3, the buffer distance L1 between the end of the traction film and the starting end of the test sample is 30 mm.

[0050] Example 3

[0051] Based on Example 1, the difference of this example is that in step S3, the buffer distance L1 between the end of the traction film and the starting end of the test sample is 40 mm.

[0052] Example 4

[0053] Based on Example 1, the difference of this example is that in step S3, the buffer distance L1 between the end of the traction film and the starting end of the test sample is 50 mm.

[0054] Comparative Example 4

[0055] Based on Example 1, the difference of this example is that in step S3, the buffer distance L1 between the end of the traction film and the starting end of the test sample is 10 mm.

[0056] Comparative Example 5

[0057] Based on Example 1, the difference of this example is that in step S3, the buffer distance L1 between the end of the traction film and the starting end of the test sample is 100 mm.

[0058] Comparative Example 6

[0059] Based on Example 1, the difference of this example is that in step S3, the buffer distance L1 between the end of the traction film and the starting end of the test sample is 150 mm.

[0060] Comparative Example 7

[0061] Based on Example 1, the difference of this example is that in step S3, the buffer distance L1 between the end of the traction film and the starting end of the test sample is 200 mm.

[0062] The peeling force tests were performed five times for each of Examples 1 to 4 and Comparative Examples 4 to 7. The results are shown in Table 2.

[0063] Table 2 Peel force test results of Examples 1 to 4 and Comparative Examples 4 to 7

[0064]

[0065] From the data in Table 2, it can be seen that the data obtained when L1 is between 20mm and 50mm has a small range, the test is stable, and the reliability is high.

[0066] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.

Claims

1. A method for testing the 180° initial peeling force of a polarizer auxiliary material, characterized in that: The steps include: Step S1, preparing a piece of glass for peeling force testing, wherein the glass is divided into an A region and a B region along a length direction, a release layer is disposed on the surface of the B region, and the length of the A region is not less than the length of the B region; Step S2, cutting the polarizer at "0°" to obtain a test sample, and the end surface of the test sample has no bubbles or white edges, and the width of the test sample is not greater than the width of area A; attaching the test sample to area A, and the gap between the test sample and the release surface of area B is less than 0.5 mm; the thickness of the test sample is greater than the thickness of the release layer; Step S3, respectively bonding the two ends of the traction tape to the end of the traction film and the starting end of the test sample near the B area to obtain a sample to be tested, wherein the distance L1 between the traction film and the test sample satisfies 10mm<L1≤50mm; and the tensile strength of the traction tape is 240-290MPa; Step S4, vertically place the sample obtained in step S3 on the clamp of the tensile testing machine, clamp the B area of ​​the glass with the lower clamp of the tensile testing machine, clamp the starting end of the traction film with the upper clamp, start the tensile testing machine after setting the speed, and record the maximum test value.

2. The method for testing the 180° initial peeling force of polarizer auxiliary materials according to claim 1, characterized in that: In step S1, the release layer is obtained by providing a glass coating or bonding a release film.

3. The method for testing the 180° initial peeling force of polarizer auxiliary materials according to claim 1, characterized in that: In step S3, the buffer distance between the end of the traction film and the starting end of the sample is 15-25 mm.

4. The method for testing the 180° initial peeling force of a polarizer auxiliary material according to claim 3, characterized in that: In step S3, the buffer distance between the end of the traction film and the starting end of the sample is 20 mm.

5. The method for testing the 180° initial peeling force of polarizer auxiliary materials according to claim 1, characterized in that: In step S4, the speed is 300 mm / min.

6. The method for testing the 180° initial peeling force of a polarizer auxiliary material according to claim 1, characterized in that: When the test sample is attached to the A region, the test sample is located in the middle of the A region.

7. The method for testing the 180° initial peeling force of a polarizer auxiliary material according to claim 6, characterized in that: The width of the test sample is half the width of region A.

8. The method for testing the 180° initial peeling force of a polarizer auxiliary material according to claim 1, characterized in that: The length of the A zone is 60-80% of the length of the glass.

9. The method for testing the 180° initial peeling force of a polarizer auxiliary material according to any one of claims 1 to 8, characterized in that: The adhesive force of the traction tape is no greater than 5gf / 25mm.

10. The method for testing the 180° initial peeling force of polarizer auxiliary materials according to claim 9, characterized in that: The adhesive force of the traction tape is no greater than 1gf / 25mm.